Kitab Mazmur: Inspirasinya bagi Kehidupan Manusia Menyejarah - Priyantoro Widodo (KHARISMATA: Jurnal Teologi Pantekosta, 2021)
The Psalms are part of The Holy Canon. This book has four synonym names. Why is that? Inn addition, this book indicates the form of poetry and so it is called Psalms number 1 to 150. This unity of 150 poetry has what meaning and importance to the life of the Christian faithful? Research on this is based on the Christian Canonical Scriptures in their final form. In order to answer the two research questions above, the researcher used the biblical library research method with the literary criticism approach. The research of Psalms biblical literature is valuable written literary data as it is owned and maintained by the community of users, so the research on it also pays attention to this phenomenon. Synonymization of the mention of the Holly Book of the Canon of the Psalms in several translations indicates the importance of the Scriptures to be revitalized by the, of faith in their lives. The Psalms are still relevant for the life of the faithful in motivating to live historically on this earth. The historical life that is meant to be true and wise with the considerations of the mind, and be firm in the decision to live in the guidance and enlightenment of the Law of God.AbstrakKitab Mazmur merupakan bagian dari kitab Kudus Kanonik. Kitab ini memiliki sebutan sinonim yang jumlahnya ada empat. Mengapa demikian? Selain itu, kitab ini mengindikasikan bentuknya berupa syair atau puisi sehingga disebut Mazmur nomor 1 hingga 150. Kesatuan syair atau puisi yang jumlahnya 150 ini memiliki makna dan kepentingan apa bagi kehidupan umat beriman Kristen? Penelitian atas hal ini dilandasakan kepada teks Kitab Kudus Kanonik Kristen dalam bentuknya yang sudah final.  Dalam rangka menjawab dua pertanyaan penelitian di atas, peneliti menggunakan metode riset pustaka biblika dengan pendekatan kritik kesusasteraan. Riset kesusastraan biblika Mazmur sebagai data sastra tulis berharga sebagaimana dimiliki dan dipelihara oleh komunitas penggunanya, maka dalam penelitian atasnya pun dengan mengindahkan fenomena ini. Sinonimisasi penyebutan kitab Kudus Kanonik Mazmur dalam beberapa terjemahan mengindikasikan kepentingan Kitab Kudus itu untuk direlevansikan oleh komunitas beriman dalam kehidupannya. Kitab Mazmur masih relevan bagi kehidupan umat beriman dalam memotivasi untuk hidup menyejarah di bumi ini. Hidup menyejarah yang dimaksud harus secara benar dan bijaksana dengan pertimbangan akal-budinya, serta teguh dalam keputusan untuk hidup dalam tuntunan dan pencerahan oleh Taurat TUHAN.